DINAMIKA HISAB TAQWIM TAREKAT SYATTARIYAH DI SUMATERA BARAT - Firdaus Sutan Mamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
Taqwim is one of the methods to determine the beginning of Ramadan taught by Shaykh Burhan al-Din Ulakan in Syattariyah Tariqa. This study is interesting to be investigated because there were some dynamical phenomena happened in West Sumatra in terms of determining the beginning of Ramadan. There was a particular society that followed the Government’s decision regarding the beginning of Ramadan, there was also a certain group of people who performed the Ramadan earlier than the Government’s decision, there was even a certain society who started the fasting one day after the Government’s decision. The more interesting one, among the adherents of Syattariyah, there were also differences to determine the first day of Ramadan. The problem is why the dynamics in determining the first day of Ramadan happened in West Sumatra. This study implemented the method of philological approach to history. From this study, it can be generated that the dynamics occur because the taqwim taught by Shaykh Burhan al-Din is not just one method to determine the beginning of Ramadan, so it is being debatedamong the adherents of Syattariyah. It has happened throughout the generation within their strong basis of thought and philosophy.